Determinan Discretionary Loan Loss Provision pada Perbankan Syariah di Indonesia - Anggraeni, Novita; Putra, Rosyid Nur Anggara (Sunan Kalijaga: Islamic Economics Journal, 2022)
This study is a quantitative study that aims to examine the effect of pre-managed earnings, capital management, leverage, sharia supervisory board, concentration ownership, and institutional ownership variables on earnings management proxied through discretionary loan loss provision. The research object used in this study were 12 Islamic banks registered with the Financial Services Authority (OJK) for the 2015-2019 period which were selected through purposive sampling technique. The data analysis technique used is panel data regression analysis using the help of the e-views software version 11. The results of this study indicate that pre-managed earnings, concentration ownership, and institutional ownership have no effect on discretionary loan loss provision. The leverage variable has a significant negative effect on the discretionary loan loss provision and the sharia supervisory board has a significant positive effect on the discretionary loan loss provision. While the capital management variable has an effect on the discretionary loan loss provision but has the opposite direction to the hypothesis in this studyKeywords: Discretionary Loan Loss Provision, Pre-managed Earnings, capital management, Leverage,  sharia supervisory board, Ownership